Desenvolvimento de um sistema de monitoração de fluidos baseado em espectroscopia de impedância - Leitzke, Juliana Padilha (2014)
Many industrial applications require monitoring the behavior of fluids, for instance, the monitoring of the kinetics of chemical reactions or the investigation of flows with multiple components (common in oil extraction and production activities). The impedance spectroscopy, i.e. the measurement of the electrical impedance at various frequencies is a technique frequently used in analytical chemistry for investigating substances. However, in industrial processes, this technique only finds limited application. This work’s main objective is the development of a simple and low-cost impedance spectroscopy measuring system, which may potentially be applied in industrial activities. First, the various techniques to obtain the impedance spectrum were revised. The system was implemented using the sequential discrete sinusoidal signal combined with transimpedance amplifier circuit for monitoring impedance of fluids. Further, a planar interdigital sensor was used for interrogation of substances. The developed system consists of a control panel on the computer connected to a signal generator and a data acquisition board. The signal generator is applied to one sensor electrode containing the substance under test and the other sensor electrode is connected to the transimpedance amplifier. The voltage output is demodulated and read by the data acquisition board. To validate the system, measurements were carried out with commercial resistors and capacitors as well as several known substances such as air, deionized water, ethylene glycol, isopropanol and oil. Ice was also measured; a substance that, unlike the others studied presents the phenomenon of relaxation in frequencies analyzed. The results are consistent with theoretical predictions and of appropriate accuracy. Hence, the system may be applied to identify different fluids, by measuring the frequency response of the impedance of substances.